If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 3) = 35 Reorder the terms: x(3 + x) = 35 (3 * x + x * x) = 35 (3x + x2) = 35 Solving 3x + x2 = 35 Solving for variable 'x'. Reorder the terms: -35 + 3x + x2 = 35 + -35 Combine like terms: 35 + -35 = 0 -35 + 3x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '35' to each side of the equation. -35 + 3x + 35 + x2 = 0 + 35 Reorder the terms: -35 + 35 + 3x + x2 = 0 + 35 Combine like terms: -35 + 35 = 0 0 + 3x + x2 = 0 + 35 3x + x2 = 0 + 35 Combine like terms: 0 + 35 = 35 3x + x2 = 35 The x term is 3x. Take half its coefficient (1.5). Square it (2.25) and add it to both sides. Add '2.25' to each side of the equation. 3x + 2.25 + x2 = 35 + 2.25 Reorder the terms: 2.25 + 3x + x2 = 35 + 2.25 Combine like terms: 35 + 2.25 = 37.25 2.25 + 3x + x2 = 37.25 Factor a perfect square on the left side: (x + 1.5)(x + 1.5) = 37.25 Calculate the square root of the right side: 6.103277808 Break this problem into two subproblems by setting (x + 1.5) equal to 6.103277808 and -6.103277808.Subproblem 1
x + 1.5 = 6.103277808 Simplifying x + 1.5 = 6.103277808 Reorder the terms: 1.5 + x = 6.103277808 Solving 1.5 + x = 6.103277808 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.5' to each side of the equation. 1.5 + -1.5 + x = 6.103277808 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + x = 6.103277808 + -1.5 x = 6.103277808 + -1.5 Combine like terms: 6.103277808 + -1.5 = 4.603277808 x = 4.603277808 Simplifying x = 4.603277808Subproblem 2
x + 1.5 = -6.103277808 Simplifying x + 1.5 = -6.103277808 Reorder the terms: 1.5 + x = -6.103277808 Solving 1.5 + x = -6.103277808 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.5' to each side of the equation. 1.5 + -1.5 + x = -6.103277808 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + x = -6.103277808 + -1.5 x = -6.103277808 + -1.5 Combine like terms: -6.103277808 + -1.5 = -7.603277808 x = -7.603277808 Simplifying x = -7.603277808Solution
The solution to the problem is based on the solutions from the subproblems. x = {4.603277808, -7.603277808}
| -2.67x-8.4=6.072+0.03x | | y=(-0.25)x+50 | | -230+2x=19+3x | | (t+z)=45z+67 | | g(X)=x-3+2 | | 2d-4=-3 | | 6x-15+4x+8=3x+9+7x-16 | | 3x+20=1500 | | 2g+7=15 | | -11+2x=19+3x | | 24x+11=123 | | -20+13x=22+11x | | 3c+2p=78 | | X-9=-3+8 | | 2b+1=-9 | | 2*-1.6+6y=-12 | | -3(7m+4)=20-5m | | 2p-4=3 | | 3x=(x-56) | | 3x+10x=5x+4x | | 7(6+3x)=105A | | 5y-3=-15 | | 25x+0.6=-30 | | 2q^2-12q=0 | | 2b+-8=2 | | 36+7n=6(5n+6)+3n | | 2(8m+3)=54 | | 2y+2=4x-2 | | 4z-7=11-2z | | 3a+2b-8a-3b= | | 7y-9=4y-12 | | 5r+20-7r=-16 |